Verbal fluency of six-year-old children assessed on the basis of the semantic category of a plant - Zając, Ewelina (Papers in Linguistics, 2025)
This article examines the verbal fluency of six-year-old children as regards the semantic category of a plant. The article analyses the collected material in reference to the number of correct and incorrect responses and the number of clusters and switches. Among the generated clusters, examples were classified into subgroups: fruit, vegetables, flowers, and cereals. A total of 27 semantic clusters consistent with the criterion were created, including 17 generated by boys and 10 by girls. There were also 116 semantic switches, including 60 generated by girls and 56 by boys, and 148 phonetic switches, including 71 generated by girls and 77 by boys. Based on the research results, conclusions can be drawn about, among other aspects, the quality of linguistic processes, the richness of vocabulary, and the level of semantic memory.